Immunomodulatory effects of Blaps rynchopetera extract - Meng, Di; Yang, Yinhe; Li, Longxing; Qian, Xiaoli; Wang, Qi; Xu, Jinglei; Zhao, Hairong; Liu, Heng; Xiao, Huai; Ding, Zhongtao (Acta cirurgica brasileira, 2022)
To explore the potential immunomodulatory effects of total extract and different polar parts from Blaps rynchopetera Fairmaire. Phagocytic activity was evaluated by neutral red assay, and the effect of the immune function was investigated by normal and immunocompromised mice models. In vitro, total extract, as well as chloroform, ethyl acetate, n-butanol and water fractions could individually enhance the phagocytic ability of mouse peritoneal macrophages; in addition, chloroform and ethyl acetate fractions had an increasing tendency when combined stimulation with lipopolysaccharide (LPS). In vivo, ethyl acetate fraction (EAF) could enhance the immune organ index, increase the serum hemolysin level and peripheral blood immune cells of immunocompromised mice, while for normal mice, the effect was inconspicuous. Blaps rynchopetera extracts had noteworthy immunomodulatory effect, especially for individuals with immune disorders.